A prospective study of lumbar facet arthroplasty in the treatment of degenerative spondylolisthesis and stenosis: cost-effective assessment from the Total Posterior Spine system (TOPSTM) IDE Study: 2-year model revision and sensitivity analyses based on 305 subjects - Ament, Jared D.; Petros, Jack; Zabehi, Tina; Yee, Randy; Johnson, J. Patrick; Vokshoor, Amir (The spine journal, 2024)
A previous cost-effectiveness analysis published in 2022 found that the Total Posterior Spine (TOPSTM) system was dominant over transforaminal lumbar interbody fusion (TLIF). This analysis required updating to reflect a more complete dataset and pricing considerations. To evaluate the cost-effectiveness of TOPSTM system as compared with TLIF based on an updated and complete FDA investigational device exemption (IDE) data set. Cost-utility analysis of the TOPSTM system compared to TLIF. A multicenter, FDA IDE, randomized control trial (RCT) investigated the efficacy of TOPSTM compared to TLIF with a current population of n=305 enrolled and n=168 with complete 2-year follow-up. Cost and quality adjusted life years (QALYs) were calculated to determine our primary outcome measure, the incremental cost-effectiveness ratio. Secondary outcome measures included: net monetary benefit as well at willingness-to-pay (WTP) thresholds. The primary outcome of cost-effectiveness is determined by incremental cost-effectiveness ratio. A Markov model was used to simulate the health outcomes and costs of patients undergoing TOPSTM or TLIF over a 2-year period. alternative scenario sensitivity analysis, one-way sensitivity analysis, and probabilistic sensitivity analysis were conducted to assess the robustness of the model results. The updated base case result demonstrated that TOPSTM was immediately and longitudinally dominant compared with the control with an incremental cost-effectiveness ratio of −9,637.37 $/QALY. The net monetary benefit was correspondingly $2,237, both from the health system's perspective and at a WTP threshold of 50,000 $/QALY at the 2-year time point. This remained true in all scenarios tested. The Alternative Scenario Sensitivity Analysis suggested cost-effectiveness irrespective of payer type and surgical setting. To remain cost-effective, the cost difference between TOPSTM and TLIF should be no greater than $1,875 and $3,750 at WTP thresholds of $50,000 and 100,000 $/QALY, respectively. This updated analysis confirms that the TOPSTM device is a cost-effective and economically dominant surgical treatment option for patients with lumbar stenosis and degenerative spondylolisthesis compared to TLIF in all scenarios examined.